Foldable Spaces: An Overt Redirection Approach for Natural Walking in Virtual Reality - Han, Jihae; Moere, Andrew Vande; Simeone, Adalberto L. (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2022)
Overt redirection is a class of virtual reality locomotion that uses perceptible transformations to enable the user to naturally walk through a virtual environment larger than the physical tracking space. In this research, we propose Foldable Spaces, a novel redirection approach based on the idea of dynamically 'folding' the geometry of the virtual environment to reveal new locations depending on the trajectory of the virtual reality user. Based on this approach, we developed three distinct techniques for overt redirection: (1) Horizontal, which folds and reveals layers of virtual space like the pages in a book; (2) Vertical, which rotates virtual space towards the user along a vertical axis; and (3) Accordion, which corrugates and flattens virtual space to bring faraway places closer to the user. In a within-subjects user study, we compared our proposed foldable techniques against each other along with a similarly situated redirection technique, Stop & Reset. Our findings show that Accordion was the most well-received by participants in terms of providing a smooth, continuous, and 'natural' experience of walking that does not involve shifts in orientation and provides an overarching view through the virtual environment.